Contemporary legal issues in relation to selected aspect of invasion of privacy in Malaysia / Mohd Fahmi Abu Fatah Sanusi ... [et al.] - Abu Fatah Sanusi, Mohd Fahmi; Ahmad Hazizi, 'Ainul Yaqeen; Ismam, Malissa Idayu; Mohd Daud, Noor Amalina (2009)
The research that was conducted is on the comparison of the law or privacy. The research looks into the various privacy issues which most impact on our daily lives, that relating to email, Mykad, photograph and media reporting. The aim of the research is to identify problems arising out from these aspects under the law of privacy and to propose recommendation to overcome those problems. Throughout the research, we discovered that there are several issues arising out of the said aspects of privacy. First, there are conflicts of rights between employers and employees in regards to email privacy. It is also noted that based on the research carried out there are issues on invasion of privacy in the implementation of MyKad in Malaysia due to the authorised and unauthorised use of personal information contained in the MyKad. The third issue is on unauthorised use of image without consent and the misappropriation of others image. Finally, we highlighted the issues on the protection of privacy at general law and by self regulation of the press against the unauthorised publication of photographs and articles which may intrude into the private lives of individuals. From the research, it is concluded that there are grey areas that remain unsettled in the law of privacy in Malaysia. Thus, recommendations are suggested for those grey areas to be resolved by the introduction of new laws in Malaysia.